Proposta de melhoria de gestão do conhecimento baseada no modelo de Bukowitz e Williams: estudo de caso em uma Instituição Federal de Ensino - Gomide, Édiron Natalli (2016)
This case study, carried out in a Federal Institution of Education, proposes a set of actions aimed at the improvement of Knowledge Management based on the results of the Knowledge Management Diagnostic (KMD) of the Bukowitz and Williams model (2002). This model investigates seven sections divided into two processes:tactical process (obtain, use, learn and contribute) and the strategic process (evaluate, build and discard). The object of this research is a public institution of basic, professional and higher education, with over 100 years of existence and operation, located in the State of Espírito Santo, Brazil. The study has a qualitative and quantitative approach, using two questionnaires as data collection tools applied to 29 managers of the organization, representing a sample of 96.67% over the universe. The collected data was treated following the instructions on the chosen model. In order to improve the analysis, facilitating the determination of the results, Knowledge Management indicators were used, as proposed by Castro (2011). As a result, we obtained a general average of 62.5% of indicators, which is considered acceptable compared to the result proposed by Bukowitz and Williams (2002).Similarly, the result of the analysis of the sections that compose the tactical and strategic processes was also considered an acceptable performance within the applied model. It was also noted that the results point to the existence of Knowledge Management practices in the institution, however, it is at an early stage. This is due to the fact that many of the daily activities in the institution are not mapped and managed in a planned and systematic way. Conclusively, based on the results found, it was possible to list a set of actions aimed at improving the implementation and management of knowledge in the studied institution, so that it is possible to provide to the managers subsidies for new models compared to the traditional public management.